The Effectiveness of Applying Coconut Coconut Oil and Lime in Reducing Stretch Marks in Second and Third Trimester Preganant Women - Sumiati, Sumiati; Andarwulan, setiana; Rihardini, Tetty; Khoirul Waroh, Yuni (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction: Stretch marks are a common complaint among pregnant women caused by excessive skin stretching. Approximately 90% of women experience stretch marks, particularly during the third trimester of pregnancy. The World Health Organization (2020) reported that out of 300,900 pregnant women globally, around 198,000 (66%) had stretch marks. In Indonesia, data from the Household Health Survey (SKRT) in 2018 showed that 67.4% of 1,000 pregnant women experienced striae gravidarum. A preliminary study at BPM Affah Fahmi found that out of 76 pregnant women observed within one week, 35 (46%) had stretch marks. Objectives: This study aims to analyze the effectiveness of the combination of coconut oil and lime in reducing stretch marks among pregnant women in their second and third trimesters. Methods: The research method used was pre-experimental with a one-group pre-test post-test design. The sample consisted of 32 randomly selected pregnant women. The treatment was administered for two months, with coconut oil applied in the morning and lime in the evening. The Atwal method was used to assess the number of stretch mark lines. Data were analyzed using the paired t-test. Results: The results of the paired t-test showed a p-value of <0.05, indicating a significant difference in the number of stretch marks before and after treatment. Conclusions: This study concludes that the use of coconut oil and lime is effective in fading stretch marks. It is recommended that healthcare providers educate pregnant women about this natural and affordable skincare method. Keywords: Stetch mark, striae gravidarum, coconut oil, lime